High Expression of MicroRNA-200a/b Indicates Potential Diagnostic and Prognostic Biomarkers in Epithelial Ovarian Cancer. (25th March 2022) - Zhang, Beilei; Li, Yi; Li, Yanhong; Zhao, Hongxi; An, Ruifang
Abstract : Objective . To detect the expression levels of microRNA-200a/b (miR-200a/b) in tumor tissues and serum of patients with epithelial ovarian cancer (EOC) and to explore its clinical significance. Methods . A retrospective selection of 30 cases of benign ovarian disease or healthy physical examination (control group) and 55 cases of EOC patients. Real-time quantitative PCR was used to detect the expression level of miR-200a/b in tumor tissues and serum, and the miR-200a/b expresses relevance in the two types of samples were evaluated at the same time. Receiver operating characteristic curve (ROC) and Kaplan-Meier survival analysis were used to evaluate the diagnostic value of miR-200a/b expression and its influence on prognosis, respectively. Results . The serum and tissue miR-200a/b expression levels in EOC patients were higher than those in the control group (P < 0.001 ), and there was a significant positive correlation between serum and tissue miR-200a/b expression (R 2 = 0.9419, P < 0.001 and R 2 = 0.9605, P < 0.001 ). ROC analysis showed that the expression of serum miR-200a/b can distinguish EOC patients from the control group. In addition, there were significant differences in the TNM stage, tumor differentiation, and lymph node metastasis between the miR-200a/b high- and low-expression groups (P < 0.05 ). Kaplan-Meier survival analysis found that the overall survival and disease-free survival of patients with high miR-200a/b expression were shorter than those of patients with low miR-200a/b expression (P < 0.05 ). Conclusion . Upregulation of miR-200a/b expression is a common molecular event in EOC patients, and miR-200a/b can be used as a noninvasive biomarker for the diagnosis and prognosis of EOC.